The High-Energy X-ray Probe (HEX-P): the circum-nuclear environment of growing supermassive black holes - Boorman, P. G.; Torres-Albà, N.; Annuar, A.; Marchesi, S.; Pfeifle, R. W.; Stern, D.; Civano, F.; Baloković, M.; Buchner, J.; Ricci, C.; Alexander, D. M.; Brandt, W. N.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
Ever since the discovery of the first Active Galactic Nuclei (AGN), substantial observational and theoretical effort has been invested into understanding how massive black holes have evolved across cosmic time. Circum-nuclear obscuration is now established as a crucial component, with almost every AGN observed known to display signatures of some level of obscuration in their X-ray spectra. But despite more than six decades of effort, substantial open questions remain: How does the accretion power impact the structure of the circum-nuclear obscurer? What are the dynamical properties of the obscurer? Can dense circum-nuclear obscuration exist around intrinsically weak AGN? How many intermediate mass black holes occupy the centers of dwarf galaxies? In this paper, we showcase a number of next-generation prospects attainable with the High Energy X-ray Probe (HEX-P 1 ) to contribute towards solving these questions in the 2030s.The uniquely broad (0.2 -80 keV) and strictly simultaneous X-ray passband of HEX-P makes it ideally suited for studying the temporal co-evolution between the central engine and circumnuclear obscurer. Improved sensitivities and reduced background will enable the development of spectroscopic models complemented by current and future multi-wavelength observations. We show that the angular resolution of HEX-P both below and above 10 keV will enable the discovery and confirmation of accreting massive black holes at both low accretion power and low black hole masses even when concealed by thick obscuration. In combination with other next-generation observations of the dusty hearts of nearby galaxies, HEX-P will be pivotal in paving the way towards a complete picture of black hole growth and galaxy co-evolution.